Downstream River Dialogues: An Educational Journey Toward a Planetary-Scaled Ecological Imagination. (March 2020) - Taylor, Affrica
Purpose: This article aims to subvert the nature/culture and subject/object divides that structure the dominant Western educational research paradigm by stepping beyond an exclusively human conversation and activating our ecological imaginations in the face of intensifying anthropogenic climate change. Design/Approach/Methods: Informed by animist ecofeminist philosophies, the river dialogues emerged from a climate action research field trip to the Athabasca oil sand mines in Alberta, Canada. They perform a "more-than-human" mode of narrative engagement with "nature in the active voice." Findings: Despite the epistemological separations of Western-style education, I conclude that we can still find ways to dialogue and learn with the nonhuman world and thereby to stimulate our ecological imaginations. Originality/Value: This article showcases innovative more-than-human narrative methods and offers a collaborative alternative to the human-centric conventions of educational research and pedagogy.